A realistic model for transverse shear stiffness prediction of composite corrugated-core sandwich structure with bonding effect. (January 2022) - Wang, Tianshu; Guo, Licheng
In this paper, a shear stiffness model for corrugated-core sandwich structures is proposed. The bonding area is discussed independently. The core is thought to be hinged on the skins with torsional stiffness. The analytical model was verified by FEM solution. Compared with the previous studies, the new model can predict the valley point of the shear stiffness at which the relationship between the shear stiffness and the angle of the core changes from negative correlation to positive correlation. The valley point increases when the core becomes stronger. For the structure with a angle of the core smaller than counterpart for the valley point, the existing analytical formulations may significantly underestimate the shear stiffness of the structure with strong skins. The results obtained by some previous models may be only 10 persent of that of the present model, which is supported by the FEM model.